What We Now Know about Race and Ethnicity - Banton, Michael (Berghahn Books, 2015)
Attempts of nineteenth-century writers to establish "race" as a biological concept failed after Charles Darwin opened the door to a new world of knowledge. Yet this word already had a place in the organization of everyday life and in ordinary English language usage. This book explains how the idea of race became so important in the USA, generating conceptual confusion that can now be clarified. Developing an international approach, it reviews references to "race," "racism," and "ethnicity" in sociology, anthropology, philosophy, and comparative politics and identifies promising lines of research that may make it possible to supersede misleading notions of race in the social sciences.